A description of dyslipidaemia and selected risk factors for cardiovascular disease in patients attending Port Elizabeth Hospital Complex - Kotze, Vanessa (Stellenbosch : Stellenbosch University, 2017)
Thesis (MNutr)--Stellenbosch University, 2017.